The effect of computer aided navigation techniques on the precision of endodontic access cavities: A systematic review and meta-analysis - P. R. Kesharani; S. D. Aggarwal; N. K. Patel; J. A. Patel; D. A. Patil; S. H. Modi (Эндодонтия Today)
AIM. To assess the impact of computer-assisted navigation techniques on the precision of endodontic access cavity preparation.MATERIALS AND METHODS. A systematic review was conducted following the PRISMA 2020 guidelines. Articles were searched for online using electronic databases, including Scopus, PubMed, Cochrane, and Web of Sciences. The success rate of root canal location using computer-aided navigation techniques in root canal access cavity preparation, along with the time required for cavity preparation and the extent of tooth substance removal were assessed in this review. After eliminating duplicate articles and applying inclusion criteria, 10 studies were chosen for analysis.RESULTS. Accuracy in location of root canal is significantly higher in the static and dynamic navigation group compared to the conventional group. Also, computer-aided static and dynamic navigation techniques removed significantly less tooth substance compared to conventional groups. Moreover, static navigation technique took significantly less time for access cavity preparation than conventional while there was no significant difference in the time taken for access cavity preparation between dynamic navigation technique and conventional technique.CONCLUSION. The root canal access cavities prepared using static and dynamic computer-aided navigation techniques are highly precise in detecting the root canal system, require less tooth substance removal, and take less time to complete.